2015
DOI: 10.1016/j.chroma.2015.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis-gas chromatography–isotope ratio mass spectrometry of polyethylene

Abstract: 8Polyethylene is probably the most used plastic material in daily life and its accurate analysis is 9 of importance. In this communication the chemical structure of polyethylenes is studied in 10 detail using conventional analytical pyrolysis (Py-GC/MS), bulk stable isotopic analysis (IRMS) 11 and pyrolysis compound specific stable isotopic analysis (Py-CSIA) to measure stable isotope 12 proportions (δ reported. To the best of our knowledge this is the first application Py-CSIA to the study of a 21 synthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Other well‐known advantages of the technique include the requirement of small sample sizes and little to no sample preparation needs. This makes analytical pyrolysis a convenient method for inexpensive and relatively rapid analyses of synthetic and bio‐based polymers including polylactic acid and polybutylene succinate plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Other well‐known advantages of the technique include the requirement of small sample sizes and little to no sample preparation needs. This makes analytical pyrolysis a convenient method for inexpensive and relatively rapid analyses of synthetic and bio‐based polymers including polylactic acid and polybutylene succinate plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis-gas chromatography/mass spectrometry was performed using a double-shot pyrolyzer (Frontier Labs. model 2020i) attached to a GC/MS system Agilent 6890N, as described by González-Pérez et al [13]. Briefly, the samples were introduced into a preheated microfurnace set at temperatures of 100 to 250°C for thermal desorption and/or at 350 to 500°C for pyrolysis.…”
Section: Pigment Extraction and Analysismentioning
confidence: 99%
“…Typical configurations of generic Py-CSIA devices have been previously described [7][8][9]. This technique has been recently used in a variety of fields from extraterrestrial OM in meteorites [7,8], soil and sediments [10][11][12][13], oil shales and petrol [14,15], polymers and food [3,16]. Therefore, Py-CSIA represents a promising technique with high potential for the study of the effect of environmental changes in subterranean environments, such as caves.…”
Section: Applied Gas Chromatography Coupled To Isotope Ratio Mass Spementioning
confidence: 99%
“…Pyrolysis compound-specific isotope analysis (Py-CSIA) combines the advantages of analytical pyrolysis (Py-GC-MS) with IRMS for the characterization of entrapped or low solubility organic compounds. In this case, the pyrolysate is directed to an isotope ratio mass spectrometer (Py-GC-C-IRMS) to measure stable isotope proportions i.e., δ 13 C, δ 15 N, of specific pyrolysis compounds [3]. Early work demonstrated that the pyrolysis process does not produce appreciable fractionation of stable isotopes and therefore the pyrolysis products are considered to be isotopically representative of the starting material [4][5][6].…”
Section: Applied Gas Chromatography Coupled To Isotope Ratio Mass Spementioning
confidence: 99%